Posttraumatic Stress Symptoms Among Polyvictimized Women in the Colombian Armed Conflict: The Mediating Role of Social Acknowledgment - González-Castro, José Luis; Ubillos-Landa, Silvia; Puente-Martínez, Alicia; Gracia-Leiva, Marcela; Arias-Rodriguez, Gina Marcela; Páez-Rovira, Darío (Frontiers in Psychology, 2021)
For decades, in a situation of armed conflict in Colombia women have suffered polyvictimization and discrimination with severe consequences that last even during the post-war peace process. This study analyses the impact on posttraumatic stress and recovery of war-related violence against women, discrimination, and social acknowledgement. A cross sectional study was conducted in 2019. Participants were 148 women with a mean age of 47.66 years (range 18-83), contacted through the NGO Ruta Pacifica de las Mujeres who had experienced significant personal violence. Results show that levels of perceived discrimination and lack of social acknowledgment are mediators in the relationship between polyvictimization and posttraumatic stress symptoms. Recognition by significant others, disapproval by family and the larger social milieu affects different PTSD dimensions and therefore how these women adapt to the effects of trauma. Findings provide strong evidence that the way society and family treats women after a traumatic event affects how the victim recovers from this event. Recognition as a victim and disapproval can coexist and be a burden for women if not adequately addressed. Results stress the importance of understanding and intervening in PTSD recovery through the analysis of social processes, and not only through and individual focus.